ANALISIS KEPRIBADIAN POLISI: FAKTOR YANG MEMPENGARUHI KINERJA POLISI DALAM MEMBANTU MASYARAKAT - Tugimin Supriyadi; Zaky Eka Hermita, Adikana Rusyda Hilmy, Sandi Dian Saputra, Ferry Ardiansya Al-Cantarra (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This Police Personality Analysis aims to determine the factors that influence police performance in helping the community. Police performance is greatly influenced by various factors, including the police's own personality. Police officers' personalities can influence how they interact with the public and how they carry out their duties. Therefore, analyzing police personality is very important in improving police performance and increasing public trust in the police. This research uses factor analysis methods to group variables that influence police performance. The research results show that of the 21 variables that influence the performance of Buleleng Regency SatPol PP employees, they can be reduced to 6 (six) factors. These factors include: (1) Work Discipline Factor, (2) Motivation Factor, (3) Job Satisfaction Factor, (4) Compensation Factor, (5) Work Environment Factor, and (6) Work Stress Factor. These factors have a significant influence on police performance, with a high work ethic, strong motivation, good job satisfaction, adequate compensation, high work discipline, good competence, a conducive work environment, an effective recruitment/selection process, and experience. relevant factors have a significant effect on police performance. In this analysis, the research also found that experience and compensation affect the performance of community-based surveillance cadres in the work area of the Pancana Health Center, Barru Regency in 2021. The most influential variables are experience and compensation for the performance of community-based surveillance cadres in Pancana Community Health Center working area, Barru Regency. In synthesis, this analysis shows that the factors that influence police performance are very complex and influenced by various variables. Therefore, this analysis suggests that police organizations need to increase the work effectiveness of police officers, build professional police institutions, and gain greater public trust by paying attention to the factors that influence police performance.